Pengaruh Lingkungan Kerja dan Beban Kerja Terhadap Kinerja Guru Sekolah Menengah Pertama Negeri 1 Kota Baru Kabupaten Karawang - Oktavia, Riska Nur; Ningsih, Karya (Universitas Respati Indonesia, 2021)
Abstract This study aims to determine the effect of Work Environment and Workload on Teacher Performance. The sampling technique used total sampling (n = 46), and data analysis techniques used Correlation and Regression with the SPSS version 22 program.The results showed that the work environment had a significant effect on teacher performance (t count = (2.295, t table 1.68107) and for workload has no significant effect on teacher performance (t count (-541, t table 1.68107). The effect of work environment and workload simultaneously affects teacher performance (F count = (10.667, F table 3.21) with a significant level of 0.05. The contribution of the influence of the Work Environment and Workload on the increase in Teacher Performance is indicated by the Adjusted R Square value of 0.301 or (30.1%) the remaining 69.9% is influenced by other variables. evaluation of the work environment, adjusted to their performance Key words: work environment, workload, teacher performance